A Study On The Causes Of Early Marriage In Patimuan Subdistrict, Cilacap Regency - Putri, Serli Dwi; Sriwanto, Sigid; Sutomo, Sutomo (Prosiding University Research Colloquium, 2021)
This study was aimed to determine the factors that cause early marriage in Patimuan Subdistrict, Cilacap Regency. This was a survey method with a population of 24 people who underwent early marriage. The purposive sampling technique was conducted by taking the female samples who underwent early marriage. An open questionnaire was used as a data collection technique. Quantitative and qualitative methods were used in the data analysis. The results showed that early marriage in Patimuan Subdistrict, Cilacap Regency was caused by low economic capability, parental supervision, pre-marital pregnancy, lack of education, religious teaching, customs, and promiscuity. The most dominant factor causing the early marriage in Patimuan Subdistrict, Cilacap Regency was parental supervision.